Socio-environmental vulnerability: analysis of bibliometric networks (Research, Society and Development, 2020)
The study on socio-environmental vulnerability is a scientific field that has been developed and worked on in several aspects, outlining the phenomenon of vulnerability in a multidisciplinary and often multifaceted way, using indicators and other tools for its analysis. In this sense, understanding and discussing the complexity that surrounds this phenomenon is a condition for effectively advancing this field of research in depth. Based on this, this article aimed to analyze bibliometric networks on the theme of socioenvironmental vulnerability and to outline an overview of publications in the period from 2009 to 2019. To do so, we used the Web of Science - WoS platform (from Clarivate Analytics), with an exploratory approach of quantitative nature adopting the bibliometric study as a research procedure. The analysis tools included VOSviewer® software version 1.6.115 and CitNetExplorer® version 1.0.0. The results show a total of 761 articles over the analyzed period, with emphasis on the significant increase in publications from 2015 with a growth rate of 61.22% in relation to the previous year. The USA is in 1st place in the ranking of publications with 273 articles. Brazil ranks 4th with 54 publications. In addition to these data, it was possible to identify the thematic and author networks, providing a series of knowledge based on the interpretations made, in which they can significantly assist in the development of other research.